Derive Law of Cosines using Pythagorean Theorem

Consider the triangle ABC. Denote h the altitude through B and D the point where h intersects the (extended) base AC
Cosine function for triangle ADB.

cos α= x/c  =>  x=c*cos α
 

Pythagorean theorem for triangle ADB
x2+h2=c2*x2+h2=c2
h2=c2−x2*h2=c2−x2

Pythagorean theorem for triangle CDB
(b−x)2+h2=a2*(b−x)2+h2=a2

Substitute h2 = c2 - x2
(b−x)2+(c2−x2)=a2(b−x)2+(c2−x2)=a2
(b2−2bx+x2)+(c2−x2)=a2(b2−2bx+x2)+(c2−x2)=a2
b2−2
bx+c2=a2b2−2bx+c2=a2

Substitute x = ccos α
b2−2b
(ccosα)+c2=a2b2−2b(c*cos α)+c2=a2

Rearrange to get Law of Cosines

a2=b2+c2−2bc*cos α

Answered by Jan M. Maths tutor

2680 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

What's the deal with Integration by Parts?


Integrate the function f(x)=lnx


Solve the equation 3sin^2(x) + sin(x) + 8 = 9cos^2(x), -180<X<180. Then find smallest positive solution of 3sin^2(2O-30) + sin(2O-30) + 8 = 9cos^2(2O-30).


Integrate (3x^2 - (1/4)x^-2 + 3) dx


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences